HIV/AIDS in the Commonwealth 2000/01 (Kensington Publications Ltd. for the Commonwealth Secretariat [London]GB, 2000)
Gives a broad overview of the progress of the disease, including the social as well as health impacts. Discusses the best current options for prevention and containment of infection, as well as for treatment and care of those infected.
Keywords: HIV